Enhancement of Psychological Factors Pertaining of New Futsal Referees - Idan, Ahmed; Al-Hilali; Alkhanfar, Farqad (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This article attempts to investigate how to enhance the psychological aspects of newly recruited futsal referees by analyzing common psychological barriers, such as anxiety, a loss of self-confidence, and pressures of making decisions. A descriptive analytical research technique was adopted, utilizing both a questionnaire and interviews administered with a group of new referees who are inexperienced. The findings revealed a significant psychological impact on referees’ performances and indicated how current programs of training often ignore this critical issue. The article encourages a blending of psychological training into referees’ development programs for enhancement of both performance and self-confidence.